Ip Man 3 [videorecording (DVD)] - Yen, Donnie, 1963-; Xiong, Dailin, 1981-; Tyson, Mike, 1966-
When a band of brutal gangsters led by a crooked property developer make a play to take over the city, Master Ip is forced to take a stand.